Measuring the risks and causes of premature death : summary of workshops - Rhodes, Holly Greenwood (The National Academies Press, 2015)
"Measuring the Risks and Causes of Premature Death is the summary of two workshops conducted by The Committee on Population of the National Research Council at the National Academies to address the data sources, science and future research needs to understand the causes of premature mortality in the United States. The workshops reviewed previous work in the field in light of new data generated as part of the work of the NRC Panel on Understanding Divergent Trends in Longevity in High-Income Countries (NRC, 2011) and the NRC/IOM Panel on Understanding Cross-National Differences Among High-Income Countries (NRC/IOM, 2013). The workshop presentations considered the state of the science of measuring the determinants of the causes of premature death, assessed the availability and quality of data sources, and charted future courses of action to improve the understanding of the causes of premature death. Presenters shared their approaches to and results of measuring premature mortality and specific risk factors, with a particular focus on those factors most amenable to improvement through public health policy. This report summarizes the presentations and discussion of both workshops"--Publisher's description